Haggai and Zechariah Research : A Bibliographic Survey - Boda, Mark, (Tools for Biblical Study, 2003)
A review of the past century of research on the biblical books of the prophets Haggai and Zechariah, with detailed analysis of the past two decades of key scholarly research and a classified bibliography of over 1200 studies. The bibliography is helpfully arranged according to topic, under more than 100 rubrics. There is a full listing of available resources for study. Altogether an extremely useful tool for all students and scholars of the Old Testament.